Global warming in an independent record of the past 130 years. Issue 1 (16th January 2013) - Anderson, D. M.; Mauk, E. M.; Wahl, E. R.; Morrill, C.; Wagner, A. J.; Easterling, D.; Rutishauser, T.
Abstract [1] The thermometer‐based global surface temperature time series (GST) commands a prominent role in the evidence for global warming, yet this record has considerable uncertainty. An independent record with better geographic coverage would be valuable in understanding recent change in the context of natural variability. We compiled the Paleo Index (PI) from 173 temperature‐sensitive proxy time series (corals, ice cores, speleothems, lake and ocean sediments, historical documents). Each series was normalized to produce index values of change relative to a 1901–2000 base period; the index values were then averaged. From 1880 to 1995, the index trends significantly upward, similar to the GST. Smaller‐scale aspects of the GST including two warming trends and a warm interval during the 1940s are also observed in the PI. The PI extends to 1730 with 67 records. The upward trend appears to begin in the early 19th century but the year‐to‐year variability is large and the 1730–1929 trend is small.